(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
ABSTRACT: The present work addresses the phenomenon of feminicide as a specific form of lethal violence practiced against females, based on the understanding and socio-historical construction of gender relations, relating this aspect to media naturalization. Given this, the research aims to understand and discuss forms of media naturalization of violent behavior and its relations with femicide. In this sense, this work will contribute to the understanding of issues related to gender violence and feminicide in which pervade the crime or sphere typified in the legislation. Therefore, it is a qualitative research that used a bibliographical study as a data collection instrument. Thus, in the discussion of the results, it was possible to perceive that the media has a strong impact on the maintenance of power relations between genders, naturalizing the place of female submission. Such naturalization, with regard to femicide, occurs through the forms of media repercussion that propagate the naturalization of male violent behavior in relation to its impact on the female gender. In this perspective, by maintaining a symbolic influence of always placing men in the spotlight or symbolic superiority, a domination is stimulated that subjects women to power or violence of different types, raised from this influence of institutions of media, social, political and familial. Keywords: Feminicide; Media naturalization; Gender.